THE ESSENCE OF ROGAN ART CAPTURING HUMAN EMOTIONS - Agrawal, Rinku; Solanki, Mishva; Chudgar, Maitree (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Rogan art, also known as Rogan painting, is a traditional art form that originated in the Kutch region of Gujarat, India. The art is characterized by its bold colors, intricate patterns, and highly stylized motifs, often depicting elements from nature, such as flowers, birds, animals, and geometric shapes. The art of Rogan painting on cloth dates back centuries. The Rogan technique was traditionally associated with the Afridi tribe of Pathans. The main aim was to combine traditional Rogan art with contemporary line work to depict human behavior and emotions through psychedelic art. This project showcases early-stage conceptual clothing that add scent to emotional fashion by amalgamating the confidence-boosting and socially acceptable aspects of fashion design with the beneficial psychological effects of mood manipulation. It investigates the expanding frontier of smell by seeking out unusual sensations that can be integrated into the fashion palette to generate radical properties that benefit the wearer. The graduate collection ’Enkrateia’ blends fashion, sustainability, and psychology. The paper explores emotional clothing and new connections with the body to discover how fashion may make a difference. It describes experimental ideas for a collection of clothes that adds function to fashion design, enhancing the quality of life for human beings suffering from stress or illnesses